PENGEMBANGAN VIDEO PEMBELAJARAN MATERI SENI PATUNG SISWA KELAS XII DI SMK NEGERI 4 PADANG - Ega Harna B; Suib Awrus (Universitas Negeri Padang, 2020)
This research aims to develop the video of sculpture Art learning with the construction techniques valid, practical, and effective class XII in vocational high school. The research uses the Research and Development method using the 4D model. The test subject of the product involves three validators including media validator, material validator, and language validator. The subject of this study is a grade XII student sculpture department with a total of 12 people. The study uses data analysis techniques such as quantitative descriptive analysis techniques and qualitative analytical techniques. The data collection methods used are interviews, documentation, and polls. The results of this study stated that the product that the author develops is valid, practical, and effectively used in the study of sculpture with construction techniques.